A new adaptable multiple-crack detection algorithm in beam-like structures - Ghadami, A.; Maghsoodi, A.; Mirdamadi, H.R. (Archives of Mechanics, 2013)
In this article, a simple method for detecting, localizing and quantifying multiple cracks in beams using natural frequencies is presented. We model cracks as rotational springs and demonstrate a relationship among natural frequencies, crack locations and depths. The main advantage of our method is that it can detect adaptably the unknown number of cracks intervened. Concise, simple calculations and good accuracy are other advantages of this method. We present a number of numerical examples for several beams to validate our method.